Hubungan Kepadatan Infiltrasi Sel Radang Limfosit dengan Klinikopatologik Karsinoma Kolorektal di RSUP Dr. Mohammad Hoesin Palembang - Calvin Ienawi; Suly Auline Rusminan; Zen Hafy (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2020)
BackgroundColorectal carcinoma has become one of primary problem that caused mortality and morbidity around the world. This malignancyhas contributed almost more than 9% of all cancer incidence. Lymphocyte infiltration density (TILs) is one of prognostic factors toevaluate colorectal cancer. Although some studies have found that there still have variations in sassociation lymphocyte density withclinicopathology of colorectal carcinoma which related to patient prognosis. This study was aimed to identify and analyze theassociation of lymphocyte density with clinicopathological colorectal carcinoma patients in Dr. Mohammad Hoesin General HospitalPalembang.MethodsA total of 41 HE stained slides which were diagnosed as colorectal carcinoma were observed under the light microscope.Lymphocytes were counted in five different areas that showed the highest lymphocytes density. The mean values of the lymphocytewere received from those five different areas. Determination of cutoff point was counted from the median of all mean value of thelymphocytes and being classified to become two categories, high-density lymphocytes and low-density lymphocytes.ResultsOut of 41 subjects, most patients have tumor size more than/or equal to 5 cm (63.4%), the tumors are often found in the left-sided ofcolon (39.0%), have moderate differentiated degree (65.9%), are included into T3 in tumor staging (48.8%), and no regional lymphnodes metastasis (39.0%). The most histopathological classification is adenocarcinoma (41.5%). Bivariate analysis showed thatlymphocyte density has correlation with tumor differentiation degree (p=0.021) and histopathological classification (p=0.004).ConclusionLymphocyte infiltration density has correlation with degree differentiation and histopathological classification of colorectal carcinomain Dr. Mohammad. Hoesin General Hospital-Palembang